Predicting factors of readiness for hospital discharge among hospitalized coronary heart disease patients at Maharaj Nakorn Chiang Mai Hospital: ปัจจัยทำนายความพร้อมในการจำหน่าย - N, Solai; R, Pudwan; W, Thongdee (Biomedical Sciences and Clinical Medicine, 2019)
Objective The purpose of this descriptive research was to identify the predicting factors of readiness for hospital discharge among hospitalized patients. Methods The Meleis’ theory of transitions was used as a framework in this research. The sample consisted of 120 patients with coronary heart disease who were admitted to the general medical ward and critical cardiovascular medical ward of Maharaj Nakorn Chiang Mai Hospital during May – December, 2015. Research instruments included questionnaire on general information, the quality of discharge teaching scale, the care coordination scale, and the readiness for hospital discharge scale. Data was analyzed using descriptive statistics, Point biserial correlation, Spearman’s rank correlation, Pearson product moment correlation and stepwise multiple regression analysis. Results The results revealed that quality of discharge teaching, care coordination, and being planned to admit were positively correlated with readiness for hospital discharge (r=.398, p<.01, r=.212, p<.05, r=.199, p<.05). Quality of discharge teaching was the only one predictor statistically affecting readiness for hospital discharge (p<.001), that accounted for the variance in the readiness for hospital discharge by 15.8 (R=.158, p<.001). Conclusion The result of this research recommends that teaching method and care coordination are important factors for patients’ perception on the hospital discharge readiness. There fore, nurses should emphasize and improve the quality of discharge teaching to promote patients’readiness for hospital discharge.